Correlation of the end-tidal CO2 value with arterial blood gas parameters – evaluation of the treatment efficacy of COPD exacerbation in the emergency department - Çakmak, Fatma; Tekin, Erdal (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Painful, invasive, and expensive arterial blood gas (ABG) analysis is required in the diagnosis, follow-up, treatment, and even discharge of patients with chronic obstructive pulmonary disease (COPD). This study aimed to compare the end-tidal carbon dioxide (ETCO2 ) value, which allows non-invasive, painless, low-cost, and continuous monitoring, with ABG parameters, in the evaluation of the treatment efficacy of COPD exacerbation. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was prospectively conducted with patients who presented to the emergency department with COPD exacerbation. ABG analysis and ETCO2 measurement were simultaneously performed in patients with COPD exacerbation at the time of arrival and after treatment, and were statistically compared. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The study included a total of 216 patients, of whom 57.4% were male. The mean age of the patients was 67.3±13.9 years. The ETCO2 values of the patients at arrival and after COPD exacerbation treatment were 39.2±10 and 37.3±9, respectively, and a statistically significant difference was determined (p=0.001). The partial pressure of pCO2 values measured at arrival and after treatment were 40.85±10.54 and 38.74±9.25, respectively, and it was statistically significant (p=0.001). A strong positive and statistically significant correlation was found between the ETCO2 and pCO2 values both at arrival and after COPD exacerbation treatment (r=0.840; p<0.001 and r=0.872; p<0.001, respectively). The Bland-Altman plot was constructed for the agreement between ETCO2 and pCO2 at both evaluation times. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. ETCO2 measurement could accurately predict the pCO2 of patients with COPD at arrival and after COPD exacerbation treatment. Also, ETCO2 may be useful in cases where pCO2 cannot be used.